Pengaruh Sexual Harassment terhadap Turnover Intention melalui Job Satisfaction pada Karyawan Perhotelan di Surabaya - Putri Widiana; Budiono Budiono (Jurnal Ilmu Manajemen, 2021)
Sexual harassment has become a global problem. Previous research has revealed that many negative impacts can be caused and affect the condition of someone who is sexually harassed. This study aimed to investigate the effect of sexual harassment on turnover intention and examine the mediating role of job satisfaction among hotel employees in Surabaya. A total of 32 hotel employees participated through a purposive non-probability sampling technique. This research uses partial least square (PLS) as its statistical analysis. The results showed a significant positive relationship between sexual harassment with turnover intention. Sexual harassment has a negative effect on job satisfaction, and job satisfaction has a negative effect on turnover intention Results also indicate that job satisfaction plays the mediator role between sexual harassment and turnover intention among Surabaya hotel employees.